ChemInform Abstract: Molten Salt Flux Synthesis and Crystal Structure of a New Open‐Framework Uranyl Phosphate Cs3(UO2)2(PO4)O2: Spectroscopic Characterization and Cationic Mobility Studies. Issue 23 (16th May 2013) - Yagoubi, S.; Renard, C.; Abraham, F.; Obbade, S.
Abstract Yellow single crystals of Cs3(UO2)2(PO4)O2 are prepared by flux melting of the precursor (UO2)3(PO4)2 (H2O)4 using excess CsI as fluxing agent (Pt crucible, 750 °C, 10 h; 7 °C/h cooling rate).